O нарушениях жилкования крыльев стрекоз (Insecta, Odonata) - Дятлова, Е.С. (Вестник зоологии, 2007)
Описана частота встречаемости аномалий жилкования крыльев в географически отдаленных популяциях Сalopteryx splendens (Harris, 1782). В популяциях массовых видов стрекоз юго-запада Украины Platycnemis pennipes (Pallas, 1771), Ischnura pumilio (Charpentier, 1825), Orthetrum brunneum (Fonscolombe, 1837), Aeshna mixta Latreille, 1805, Crocothemis erythraea (Brulle2, 1832) также обнаружены особи с нарушениями жилкования крыльев. Приведены изображения и описания крыльев, отличающихся от нормальных. Высказаны предположения о причинах возникновения различных нарушений жилкования крыльев у стрекоз. The frequency of occurrence of wings abnormalities in the distant populations of Ñalopteryx splendens (Harris, 1782) is described. Odonata with abnormalities of the wing venation are recorded in the populations of abundant species Platycnemis pennipes (Pallas, 1771), Ischnura pumilio (Charpentier, 1825), Orthetrum brunneum (Fonscolombe, 1837), Aeshna mixta Latreille, 1805, Crocothemis erythraea (Brulle´, 1832) in the South-Western Ukraine. Abnormal wings are figured and described. Possible causes of the wing abnormalities are discussed.